2007
DOI: 10.1039/b710066c
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic kinetic and kinetic resolution of N-Boc-2-lithiopiperidine

Abstract: Asymmetric substitution of 2-lithiopiperidines can be achieved by dynamic resolution; the organolithium is formed as a racemic mixture by proton abstraction (or tin-lithium exchange) and is resolved in the presence of a chiral ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
0
14
2
Order By: Relevance
“…This was presumably due a lack of coordination of Fe to the substrate, which might also indicate that no imine intermediate is involved in this specific case. Despite the excess substrate required, the Cu-catalyzed methodology for the coupling of unprotected tetrahydroisoquinoline was extended to the coupling with pyrroles 316-318, yielding products 319-321 in moderate yield (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)Scheme 74). The role of the oxidant was examined and studies performed in the absence of oxi-dant with a stoichiometric quantity of Cu (irrespective of its oxidation state) or with TBHP as oxidant in the absence of Cu, showed no product formation, suggesting that the oxidant is not only required to reoxidize Cu I to Cu II in the catalytic cycle.…”
Section: Reaction Of Nucleophiles With An A-amino Cation (Iminium)mentioning
confidence: 99%
See 1 more Smart Citation
“…This was presumably due a lack of coordination of Fe to the substrate, which might also indicate that no imine intermediate is involved in this specific case. Despite the excess substrate required, the Cu-catalyzed methodology for the coupling of unprotected tetrahydroisoquinoline was extended to the coupling with pyrroles 316-318, yielding products 319-321 in moderate yield (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)Scheme 74). The role of the oxidant was examined and studies performed in the absence of oxi-dant with a stoichiometric quantity of Cu (irrespective of its oxidation state) or with TBHP as oxidant in the absence of Cu, showed no product formation, suggesting that the oxidant is not only required to reoxidize Cu I to Cu II in the catalytic cycle.…”
Section: Reaction Of Nucleophiles With An A-amino Cation (Iminium)mentioning
confidence: 99%
“…The analogous 2‐lithiopiperidines have also been successfully resolved to access α‐functionalized piperidine derivatives enantioselectively. In a series of experiments, Coldham and co‐workers studied the effect of several chiral diamine ligands, initially used for the dynamic resolution in pyrrolidine systems, on the dynamic resolution of N ‐Boc‐2‐lithiopiperidine 32. Racemic 44 a prepared by proton abstraction of 42 and reaction with Bu 3 SnCl was followed by transmetallation to generate 56 (Scheme ).…”
Section: Reaction Of Nucleophiles With An α‐Amino Anion Speciesmentioning
confidence: 99%
“…Investigation of a range of other chiral ligands known to promote enantioselective lithiation substitutions, including a trans-cyclohexane-1,2-diamine pioneered by Alexakis and dipeptides used by Beak and Coldham similarly failed to provide products in satisfactory enantioenrichments. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] We hypothesised that this may be due to configurational instability of the lithiated tetrazole intermediate -a Hoffman test using racemic and (S)-2-(dibenzylamino)-1,3-diphenylpropan-1-one as electrophiles confirmed that this is the case (for full details of ligand screen and Hoffman test, see ESI). 45 Scheme 7.…”
Section: Scheme 2 Electrophile Scopementioning
confidence: 85%
“…On the basis of different experiments, the authors suggested that a dynamic thermodynamic resolution [31] is operating in the process. Furthermore, asymmetric substitution of N-Boc-2-lithiopyrrolidine [32] and N-Boc-2-lithiopiperidine [33] were achieved by dynamic resolution in the presence of a chiral ligand (such as 39, 40 and 42). Similarly, highly stereoselective asymmetric substitution reactions of -sulfenyl carbanions were reported employing bisoxazoline chiral ligands 44 [34].…”
Section: Transmetallation: Tin/lithium Exchangementioning
confidence: 99%